PERILAKU IBU DALAM IMUNISASI DASAR LENGKAP DI PUSKESMAS GAYAM KABUPATEN SUMENEP - Miftahol Hudhah Hudhah; Atik Choirul Hidajah (Universitas Airlangga, 2017)
Immunization is an effort to boost the immunity of someone actively against a disease, so when exposed to the disease will not get sick or only experience a mild ache. The main goal of immunization is to lower of pain, disability and death due to diseases that can be prevented by Immunization (PD3I). To achieve these objectives it must achieve coverage of the basic immunization of 91%. The achievement of basic immunization at the Gayam health center does not meet the target. One of the causes is not achieving the target because of the mother foctor in immunizated his son. This study was conducted to describe and analyze the relationship factors of mother in the achievement of basic immunization in region work of Gayam health center Sumenep regency. This study use cross sectional design. The subject were taken from a population by simple random sampling technique. The independent variables in this study were the age of mother, mother's level of education, occupation of mother, mother's level of knowledge, maternal attitudes and beliefs of mother. The results showed that the variables that associated in the achievement of basic immunization are mother's level of education (p = 0,020), mother's knowledge level (p = 0,000), beliefs of mother (p = 0.000) and the maternal attitudes (p = 0.000). While the variable age of mother and occupation of mother not associated in the achievement of basic immunization because the p value > 0.05. Conclusion of this study is factors of associated in the achievement of basic immunization are mother's level of education, mother's knowledge level, beliefs of mother and maternal attitudes. Therefore it is necessary for the addition of knowledge’s mother through the delivery of information, in addition health workers provides an explanation to the mother related to the incidence of post followup immunization so that mothers believe that immunizations have an impact well and the mother was able to behave better towards immunization.Keyword: basic immunization, beliefs of mother, maternal attitudes, mother's knowledge level, mother's level of education